2021
DOI: 10.21037/qims-20-5
|View full text |Cite
|
Sign up to set email alerts
|

Association between anterior talofibular ligament injury and ankle tendon, ligament, and joint conditions revealed by magnetic resonance imaging

Abstract: Background: The lateral ankle ligament complex is the most frequently injured ligament secondary to strong ankle inversion movement during lateral ankle sprains (LAS). Among these injuries, anterior talofibular ligament (ATFL) injury is the most frequent condition (present in 66-85% of such injuries). The purpose of this research was to use magnetic resonance imaging (MRI) to determine the association between ankle tendon, ligament, and joint conditions and ATFL injuries.Methods: A case-control MRI study was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Furthermore, an oblique PDw sequence was measured with a matrix of 448 px × 359 px; a TR of 1800 ms; a TE of 29 ms; a slice thickness of 2.5 mm; and a 45° angulation with respect to the tibial plafond [ 7 , 8 , 9 ]. Patients were scanned at a 1.5-T field strength (Magnetom Aera; Siemens Healthineers, Erlangen, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, an oblique PDw sequence was measured with a matrix of 448 px × 359 px; a TR of 1800 ms; a TE of 29 ms; a slice thickness of 2.5 mm; and a 45° angulation with respect to the tibial plafond [ 7 , 8 , 9 ]. Patients were scanned at a 1.5-T field strength (Magnetom Aera; Siemens Healthineers, Erlangen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The most affected ligament is the anteroinferior tibiofibular ligament (AITFL), whereas the involvement of the posteroinferior tibiofibular ligament commonly exhibits a pattern of bony avulsion [8]. Moreover, associated ankle injuries, for example, to the calcaneofibular ligament, are displayed more often in case of AITFL injury [9], potentially resulting in peroneal muscle atrophy [10] and ankle instability [11]. To reliably evaluate the tibiofibular syndesmosis, magnetic resonance imaging (MRI) is the method of choice [6].…”
Section: Introductionmentioning
confidence: 99%
“…Lateral ankle ligament complex injuries (anterior talofibular ligament (ATFL), calcaneofibular ligament (CFL), and posterior talofibular ligament (PTFL)) are present in up to 85% of ankle sprains, making them the most frequently injured ligaments secondary to strong ankle inversion movement during lateral ankle sprains [5]. PTFL injury is infrequent, on the other hand, ATFL is considered as the principal injured ligament followed by the CFL [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Destruction of the joint due to septic arthritis results in functional instability and changes in lower limb muscle activity patterns during unexpected disturbances, particularly in proximal muscles rather than distal muscles [ 12 ]. In addition, according to a study by Casado-Hernández et al [ 13 ], patients with anterior talofibular ligament (ATFL) injuries showed a greater presence of calcaneofibular ligament and tibiotalar joint injuries than subjects with non-injured. These constitute the rationale that functional instability can lead to more severe joint destruction, which accelerates the patient’s limping and pain and intensifies discomfort.…”
Section: Introductionmentioning
confidence: 99%